Transfer accuracy of partially enclosed single hard vacuum-formed trays with 3D-printed models for lingual bracket indirect bonding: A prospective in-vivo study - Viet Anh Nguyen; Thuy Anh Nguyen; Hong Le Doan; Thi Hanh Pham; Bich Ngoc Doan; Thi Thanh Thuy Pham; Viet Hoang (PLoS ONE, 2025)
Objective This study aims to evaluate the clinical transfer accuracy of partially enclosed single hard vacuum-formed trays based on three-dimensional (3D) printed models for lingual bracket indirect bonding. Materials and methods Thirty-two consecutive patients receiving lingual orthodontic treatment were enrolled. Digital models with ideal bracket positions were 3D-printed, followed by fabrication of partially enclosed single hard vacuum-formed trays. Digital impressions captured actual bracket positions and were compared to the ideal positions. One-tailed t-tests assessed if errors were within clinically acceptable thresholds of 0.5 mm for linear measurements and 2° for angular measurements. Results Mean bracket transfer errors were 0.052 mm, 0.076 mm, 0.106 mm, 0.795°, 1.344°, and 2.485° for mesiodistal, buccolingual, occlusogingival, rotation, tip, and torque, respectively. Transfer errors were statistically below the clinically acceptable thresholds for all dimensions except torque. Frequencies of acceptable transfer errors were 100%, 100%, 99.3%, 93.1%, 78.3%, and 54.0%, respectively. Conclusion Partially enclosed single hard vacuum-formed trays with 3D-printed models transfer lingual brackets with high accuracy in the mesiodistal, buccolingual, and occlusogingival dimensions, rotation, and tip. However, the transfer of torque remains questionable.